Tanggapan Pertumbuhan dan Hasil Tanaman Bawang Daun (Allium fistulosum L.) terhadap Aplikasi Pupuk Organik Cair Urin Kambing - Sulkifli Nurdin; Febianus Sapitu; Nober Padidi (JURNAL AGROPLASMA, 2026)
Scallions are high-value economic crop that contains essential nutrients and minerals that support health. This study aimed to determine the effect of various concentrations of liquid organic fertilizer derived from goat urine on the growth and yield of scallions. The research was conducted in Tongko Village, Baroko Subdistrict, Enrekang Regency, from April to July 2025. The Complete Randomized Block Design (CRBD) Single-Factor method was applied in this study, using five different treatments and six replicates. The concentrations of liquid organic fertilizer tested include 0% (0 ml.l-1), 2.5% (25 ml.l-1), 5% (50 ml.l-1), 7.5% (75 ml.l-1), and 10% (100 ml.l-1). The data obtained were analyzed using analysis of variance, followed by the Least Significant Difference test at α 5% significance level. The results showed that applying liquid organic fertilizer derived from goat urine did not affect scallion plant height and leaf number. However, it substantially impacts the fresh and economic weight of the plants, with a concentration 10% (100 ml.l-1) being the best for enhancing the growth and yield of scallions. Further research is recommended to test higher concentrations to achieve maximum scallion growth and yield under field conditions.Keywords: concentrations, goat urine, liquid organic fertilizer, scallion